2014
DOI: 10.3855/jidc.3147
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to influenza A(H1N1)v in HIV-infected patients

Abstract: Introduction: HIV infection is considered a risk factor for severe outcomes of influenza A(H1N1)v infection. However, data on immune response against influenza A(H1N1)v virus in HIV-infected patients are lacking. Methodology: Data from seven HIV-positive and 14 HIV-negative patients infected with A(H1N1)v and from 23 HIV-positive and six HIV-negative asymptomatic controls were analyzed to evaluate the clinical picture, A(H1N1)v viral shedding, and the immune response against the virus. Results: Patients displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Instead, persistent existence of IgM antibody indicated that impaired immune system in the HIV-infected patient resulted in delay of viral shedding. In fact, HIV-infected patients showed a poor response of specific antibodies and reduced ability of clearance of influenza virus [26].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, persistent existence of IgM antibody indicated that impaired immune system in the HIV-infected patient resulted in delay of viral shedding. In fact, HIV-infected patients showed a poor response of specific antibodies and reduced ability of clearance of influenza virus [26].…”
Section: Discussionmentioning
confidence: 99%
“…Transmission from asymptomatic patients is serious in the context of South Africa's high HIV prevalence. While studies have demonstrated that HIV-infection status alone in adults does not increase risk of Influenza infection, evidence suggests that prolonged Influenza shedding periods (> 1 week) can be observed in patients exhibiting non-HIV related immunosuppression [62,63]. Such prolonged influenza positivity was exhibited in patient 1.1 Phylogeny as a Utility to Observe Influenza Nosocomial Transmission a, who remained influenza PCR positive for 15 days.…”
Section: Discussionmentioning
confidence: 99%
“…Age and comorbidity were chosen a priori as potential confounders. Therefore, they were both kept into the model, since these variables are associated with increased susceptibility to influenza (Madjid, Aboshady et al 2004, Kurai, Saraya et al 2013, Sansonetti, Sali et al 2014, McElhaney, Garneau et al 2015, Bahadoran, Lee et al 2016.…”
Section: Influenza Vaccine Effectivenessmentioning
confidence: 99%